TO BE VISIBLE OR NOT TO BE VISIBLE: AN ANALYSIS OF WOMEN'S COOPERATIVES' USE OF NEW MEDIA (Third Sector Social Economic Review, 2025)
The women's cooperative movement in Turkey started in the early 2000s with the aims of valorising women's labour, preventing women's poverty, and empowering women, and today different types of women's cooperatives have been established. In the following years, Simurg Women's Cooperatives Association (SIMURG) was established under the leadership of 7 women's cooperatives in order to increase communication and cooperation among women's co-operatives. This study aims to examine the corporate identity of SIMURG founder cooperatives (n=7) and to determine their use of new media, which has become one of the important tools of corporate communication. The research was conducted using the case study technique and the Instagram accounts, Facebook pages and websites of the cooperatives were subjected to descriptive analysis according to the criteria determined by using the document analysis method to collect data. It was found that multiple searches were required in order to identify women's cooperatives' corporate identity (where and when they were established, areas of activity, etc.). It is not possible to access the identities of cooperatives through a single website or social media account. On the other hand, it was observed that women's cooperatives use social media, one of the new media tools, mostly to promote their products or services and to announce the events they participate in/organise. In addtion, it was found that they do not use social media actively enough, the number of posts is low, and the photos are not aesthetically pleasing. Only two of the cooperatives in the sample have corporate e-commerce websites, while the others sell their products through KEDV's social enterprise (nahil.com.tr)
Keywords: Women’s cooperatives; cooperatives; social media; new media; gender